The Modulatory Effect of Physical Activity on APE1-Mediated Telomere Length and Stability; A Narrative Review - Gabriela Betlej; Aleksandra Kwiatkowska; Ewelina Bator (Central European Journal of Sport Sciences and Medicine, 2019)
Physical activity is associated with enhanced generation of reactive oxygen species (ROS) that, in turn, can play a dual role in the human body. Upon physiological conditions, ROS act as secondary messengers in different cell signaling pathways. In contrast, ROS overexpression can lead to oxidative stress and oxidative stress-associated harmful consequences. This exercise-induced interplay among oxidants and antioxidants can modulate numerous physiological and molecular mechanisms, for example telomere length maintenance and stability. The latter is, in turn, under strict control of oxidative stress-activated base excision repair (BER) pathway, one of the DNA repair mechanisms; and growing evidence directs attention to apurinic/apyrimidinic endonuclease 1 (APE1), a multifunctional BER protein. Therefore, this review intends to address several issues concerning modulatory effect of exercise on APE1-mediated telomere length maintenance and redox activities.